Analysis of Policies on Teacher and School Principal Performance Management In Indonesia: A Literature Review - Hevardani, Kelly Angelly; Hadiyanto; Gistituati, Nurhizrah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
Effective performance management of teachers and school principals is a critical determinant of educational quality and institutional accountability. This study analyses national policies and regulatory frameworks governing performance management within the education sector, drawing upon official policy documents, national regulations, and implementation reports. Employing a literature-based and policy analysis approach, the study identifies significant gaps between policy formulation and practical implementation at the school level. The findings reveal persistent challenges, including limited comprehension of performance indicators, inadequate monitoring and evaluation mechanisms, and insufficient resource support. The analysis underscores the need to strengthen managerial competencies, enhance professional development, and establish equitable and sustainable performance evaluation systems. Overall, the study highlights the importance of developing a more adaptive and context-responsive performance management model to promote continuous improvement in educational quality and leadership effectiveness.